Peran KPK dalam Memberantas Korupsi di Indonesia: Analisis terhadap UU Nomor 19 Tahun 2019 tentang Komisi Pemberantasan Korupsi dalam Tinjauan Fiqh Siyasah Dusturiyah - Br Tarigan, Anisa Tiara; Irham, M. Iqbal (Nagari Law Review, 2023)
The aim of this research is to examine the role of the Corruption Eradication Commission (KPK) in overcoming corruption in Indonesia from the perspective of Fiqh Siyasah Dusturiyah. This study analyzes Law No. 19 of 2019 to understand the legal basis, duties, performance and function of the Corruption Eradication Committee in eradicating corruption, including the methods and strategies used. The document analysis method is used as a research plan with a focus on literature related to Law No. 19 of 2019. This research is a type of normative legal research using descriptive methods. The data collection used in this research is primary data and secondary data, the primary data is Law No. 19 of 2019, while the secondary data is taken from research results and opinions of legal experts. The research results show that the Corruption Eradication Commission has the responsibility and authority to eradicate corruption based on the Corruption Eradication Commission Law No. 19 of 2019. The Corruption Eradication Commission is a special police agency that strengthens efforts to eradicate corruption in Indonesia. However, Law No. 19 of 2019 received public opposition and criticism because it fundamentally changed the duties and authority of the Corruption Eradication Commission, especially in its implementation. In reviewing the fiqh siyasah dusturiyah, the Corruption Eradication Commission (KPK) is expected to be able to maintain justice and stability in the country through fair, equal and effective law enforcement. The KPK is also considered to have a moral responsibility to protect public interests and prevent criminal acts of corruption.